The role of 'pracademics' in education and development of adventure sport professionals. Issue 1 (2nd January 2019) - Collins, Loel; Collins, Dave
ABSTRACT: Understanding and exploiting the synergy between theory and practice lies at the heart of effective education for outdoor professionals. Accordingly, and in an attempt to stimulate debate, this paper conceptualizes the interaction between theory and practice in the context of the education of outdoor professionals. We identify issues specific to the often separated worlds of practice and academia. While acknowledging those distinct skills and competencies, however, we also explore a mid-role; that of the 'pracademic' or scientist–practitioner or practitioner scholar, considering behaviours that may encourage greater collaborative work to inform the process and implementation of the education of outdoor professionals.